Pengenalan Vertikal Garden Sebagai Solusi Penataan Lingkungan dan Tanaman Berkhasiat Obat Sebagai Peluang Usaha Rumah Tangga - Dining Aidil Candri; Arben Virgota; Hilman Ahyadi; Baiq Farista (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
The vertical garden is a garden that is designed using a separate structural system so that it can be erected or affixed to the wall. The principle of making a vertical garden must meet the requirements consisting of sunlight, types of plants, and water used. In addition, the manufacture of vertical gardens can use media such as bottles that are not used. The vertical garden is one way to improve land-use efficiency. Several types of plants can be grown using the vertical garden method, such as food crops, ornamental plants, and medicinal plants. Plants that have medicinal properties are now quite easy to find growing around the house. Medicinal plants are types of plants in which certain parts of the roots, stems, bark, leaves are believed to relieve or reduce pain. Therefore, this activity was carried out to introduce the technique of planting vertical gardens and several types of plants that can be planted with this technique, one of which is medicinal plants